The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s13099-018-0276-3
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota profile in new-onset pediatric Crohn’s disease: data from a non-Western population

Abstract: BackgroundThe role of microbiota in Crohn’s disease (CD) is increasingly recognized. However, most of the reports are from Western populations. Considering the possible variation from other populations, the aim of this study was to describe the microbiota profile in children with CD in Saudi Arabia, a non-Western developing country population.ResultsSignificantly more abundant genera in children with CD included Fusobacterium, Peptostreptococcus, Psychrobacter, and Acinetobacter; whereas the most significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 47 publications
6
32
0
Order By: Relevance
“…The current data was also aligned with previous reports of decreased Ruminococcus spp. in IBD patients [33]. Methanobrevibacter smithii, an archaea methanogen, was significantly decreased in IBD patients [36].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The current data was also aligned with previous reports of decreased Ruminococcus spp. in IBD patients [33]. Methanobrevibacter smithii, an archaea methanogen, was significantly decreased in IBD patients [36].…”
Section: Discussionmentioning
confidence: 92%
“…We found that F. prausnitzii was negatively associated with fecal calprotectin, EPX, and IgA in the current study. The Roseburia genus [23,[30][31][32][33] or specific species (e.g., Roseburia intestinalis and Roseburia hominis) [34,35] were significantly decreased in patients with IBD. In our analysis, Roseburia spp.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…OTU-1: Acinetobacter, which was present in all macrophage samples of the mucosal lamina propria of the Crohn's disease inflamed intestinal tract and was the largest observed by the average read number, was a genus that was significantly increased compared to normal in the 16S rRNA analysis of fecal and mucosal samples www.nature.com/scientificreports www.nature.com/scientificreports/ of newly developed Crohn's disease cases in 17 children 25 . In addition, it has been reported that some of the Acinetobacter genus showed digestion resistance in a human macrophage cell line and enhanced production of IL-1β, IL-6, and TNF-α by macrophages 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The development of various diseases such as type 2 diabetes, colorectal cancer (CRC), inflammatory bowel diseases and even depression, which is seemingly unrelated to the gut, has been discussed as being linked to the composition of the intestinal microbiome [1][2][3][4][5][6][7][8][9]. For example, Fusobacterium nucleatum has been identified as playing multiple roles in the development of CRC or its treatment [10], such as augmenting CRC cell proliferation [11] or increasing resistance to chemotherapy [12].…”
Section: Introductionmentioning
confidence: 99%